Analysis of Home-Based Factors and Student Personal Attributes Influencing Transition Rate by Gender from Primary to Secondary Schools in Kisii Central SubCounty, Kenya - Truphena Nyangara Onyango,; Christopher Makworo Ayienda , (IJRDO- Journal of Educational Research, 2020)
The flow of students from primary to the secondary level of education known as transition is an indication of balanced and unbalanced development of education between two levels. A large number of primary school graduates fail to proceed to secondary level of education all over the world because of a number of factors. The causes may be school-based factors, home based factors or students’ based factors/attributes. The purpose of this study was to establish the home based factors and student personal attributes influencing transition rates from primary to secondary school in Kisii Central Sub-County. The study design of the study was a descriptive survey research design. The study population comprised of all the 48 secondary schools in Kisii Central Sub-County. Out of the targeted population, a sample of11 schools was drawn through the process of stratified random sampling technique. A sample size from a target population of 5422 students and 288 teachers was then be used to select a sample of 542 form one students and 29 teachers from the sampled schools. Stratified random sampling technique was then used to determine the sample size per school, based on gender for form one students and teachers in each division. In addition all the 38 Head teachers in the sampled schools were used in the study. Structured and unstructured questions were used in the study. The study established that generally there was an increase in the number of pupils who enrolled for KCPE and those who joined form one. However, there was a general drop in the number of girls who sat for KCPE and those who joined form one. Also, the study established that home-based factors positively and significantly influence transition rates while student’s personal factors influence negatively transition rate in terms of enrolment, dropout and academic performance of students. The study recommended that: The government should continue enforcing the policy on 100% transition rate and any parent contravening this policy should be prosecuted; The community and the family at large should ensure that they support students by advising them appropriately on the importance of education to minimize dropout and increase performance of their students; and the learners should develop intrinsic motivation towards education that will push them towards achieving highest level of academic achievement.